Reorganization of work schedules for better distribution of work demands in home health care – a feasibility study - Maja Vilhelmsen; Tonje Pedersen Ludvigsen; Kristina Thomassen; Charlotte Diana Nørregaard Rasmussen (BMC Health Services Research)
Abstract Background Given the home health care industry’s growth, increasing demand for workers, and complex patient care needs, investigating initiatives to maintain home health care workers’ health and ability to work is crucial. This study aims to assess the feasibility of an organizational intervention for equal distribution of physical and psychosocial work demands among home health care aides. Method We conducted a 7-week quasi-experimental feasibility study at a Danish home health care institution with 27 home health care aides. The 6SQuID framework was used to develop, test and evaluate the feasibility of the organizational intervention, inspired by the ‘Goldilocks Work Principle’. The intervention consisted of three activities: (1) classification workshop, (2) individual dialogue with a schedule coordinator, and (3) reorganizing work schedules. Feasibility was assessed through: (1) acceptability evaluated by interview and questionnaire post-intervention, (2) fidelity assessed by documentation during intervention, and (3) potential effects on selected psychosocial factors and physical work demands evaluated pre-post intervention with technical measurements and questionnaire. Results Nineteen home health care aides participated in the evaluation of the intervention. Most of the home health care aides (73.33%) reported to like or really like the intervention. The interviewees expressed general acceptance of both the intervention activities and the overall aim of the intervention. Most home health care aides (77.8%) participated in the Classification workshop and 124 citizens were classified. All home health care aides participated in the Individual dialogue. No significant changes were seen in the Reorganized work schedules (p > 0.05). Physical and emotional fatigue and physical exertion showed statistically significant change (p < 0.05), with a mean difference of 17 and 11 (100 point scale), and 1.7 (10 point scale) points respectively. Conclusion This study found components of the intervention to be feasible, but concludes that adaptions to enhance implementation addressing barriers related to time pressure, improving fidelity to the intervention, and ensuring practical applicability within the home health care context are critical for future success. Trial registration The study was registered in the ISRCTN registry under registration number ISRCTN15131198 on August 8, 2023.